Analysis of Road Damage Using Road Condition Survey Data and Handling Designs (Case Study of the Pasangkayu - Baras Section) - Setiawan, Arman; Putu Artawan, I; Yuniarto, Eko; Bachtiar, Erniati; Yudha Alam , Gigih (ASTONJADRO, 2024)
Inventory data and road conditions are the main road network data for measuring and monitoring road network conditions, making predictions of future conditions, and assisting in the strategic decision making process in road network management. This data is also the main data in general road network planning, programming and budgeting, research to evaluate the condition of road pavement to evaluate the condition of road pavement according to the level of damage so that later the budget can be determined. Data collection on road conditions uses a survey vehicle called Mata Garuda (MAGARU). The data obtained from MAGARU is road network data/RNI, pavement condition data/PCI and road unevenness data/IRI. Testing using the Benkelman Beam (BB) tool at 100 m intervals. Collecting traffic enumeration data uses CCTV equipment installed on the road section with an observation period of 7 x 24 hours. The results of the analysis showed that the proposed type of treatment was Preventive with an average value of 3.7, Minor Rehabilitation with an average value of 5.4 and Major Rehabilitation with a value of 8.8. For the PCI survey analysis, Preventive Treatment was obtained with an average value of 87.5, Minor Rehab with an average value of 65.3 and Major Rehab with an average value of 27.5. For the analysis of the deflection survey, a value of > 0.4 was obtained so the treatment was Major Rehab. The CESA4 value is 4,059 x 106 and the CESA5 value is 5,546 x 106. The results of pavement calculations show that Preventive Treatment uses Thin Layer Asphalt Concrete (LTBA), Minor Rehab uses Asphalt Concrete Wearing Course (AC-WC), Major Rehab uses Asphalt Concrete Wearing Course ( AC-WC), Asphalt Concrete Binder Course (AC-BC) and Asphalt Concrete Binder Course Leveling (AC-BC Lev).